Comparison between composites reinforced with natural and synthetic fibers : Part I - Nimir, Yassin Lutfi Mahmud (IIUM Press, 2011)
In this chapter, a detail description of fabrication of jute/epoxy, glass/epoxy, and jute/glass/epoxy hybrid composite is given. Overall procedures and methods are discussed in details before conducting the mechanical tests